Proinflammatory cytokines contribute to development and function of regulatory T cells in type 1 diabetes. (21st November 2012) - Thomas, Helen E.; Graham, Kate L.; Chee, Jonathan; Thomas, Ranjeny; Kay, Thomas W.; Krishnamurthy, Balasubramanian
Abstract : Type 1 diabetes is caused by immune‐mediated loss of pancreatic beta cells. It has been proposed that inflammatory cytokines play a role in killing beta cells. Expression of interleukin (IL)‐1 and tumor necrosis factor (TNF‐α) has been detected in islets from patients with type 1 diabetes, and these cytokines can induce beta cell death in vitro . We produced nonobese diabetic (NOD) mice lacking receptors for these cytokines. Islets from mice lacking IL‐1RI or TNFR1 were killed when transplanted into wild‐type NOD mice, suggesting that cytokine action on beta cells is not required for killing. Mice lacking TNFR1 did not develop diabetes, and mice lacking IL‐1R had delayed onset of diabetes, indicating a role for these cytokines in disease development. TNFR1‐deficient mice had an increased number of CD4 + CD25 + FoxP3 + regulatory T cells with enhanced suppressive capacity. IL‐1 was produced at higher levels in NOD mice and resulted in dilution of suppressor function of CD4 + CD25 + FoxP3 + regulatory T cells. Our data suggest that blocking inflammatory cytokines may increase the capacity of the immune system to suppress type 1 diabetes through regulatory T cells.